Influence of Urbanization on Epiphytic Bacterial Communities of the Platanus × hispanica Tree Leaves in a Biennial Study - Espenshade, Jordan; Thijs, Sofie; Gawronski, Stanislaw; Bové, Hannelore; Weyens, Nele; Vangronsveld, Jaco (Frontiers in Microbiology, 2019)
The aerial surfaces of plants harbour diverse communities of microorganisms. The rising awareness concerning the potential roles of these phyllosphere microbiota for airborne pollutant remediation and plant growth promotion, advocates for a better understanding of their community structure and dynamics in urban ecosystems. Here, we characterised the epiphytic microbial communities on leaves of Platanus x hispanica trees in the city centre of Hasselt (Belgium), and the nearby forest area of Bokrijk, Genk (Belgium). We compared the influences of season, site, and air pollutants concentration variations on the tree’s phyllosphere microbiome by determining the intra- and inter-individual variation in leaf bacterial communities. High-throughput amplicon sequencing of the 16S rRNA gene revealed large variation in the bacterial community structure and diversity throughout the years but also allowed to discriminate an environment effect on community assembly. Partial drivers for this environment effect on composition can be correlated with the huge differences in ultrafine particulate matter (UFP) and black carbon on the leaves. A change in bacterial community composition was noted for trees growing in the city centre compared to the natural site, and also more human-associated genera were found colonising the leaves from the city centre. These integrated results offer an original and first insight in the Platanus phyllomicrobiota, which can offer new opportunities to use phyllosphere microorganisms to enhance air pollution degradation.